2010
DOI: 10.1002/mame.200900425
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Fiber Repulsion in Multijet Electrospinning for Higher Throughput

Abstract: A novel electrospinning set‐up has been developed to successfully electrospin multiple jets with controlled fiber repulsion using a plastic filter. This set‐up shows reduced fiber repulsion as compared to a multineedle set‐up, along with increased throughput. The effect of processing parameters on the fiber repulsion in a multineedle set‐up was also studied. It was found that fiber repulsion could be reduced by controlling emitter voltage and emitter/collector distance. Other important parameters studied inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…Recently reported modifications of multi-jet electrospinning (MES) systems in order to overcome the mutual repulsion effect of polymer solution jets include application of additional electrodes, auxiliary electrodes and specifically designed polymer nozzles arrays [21,24,34]. Most of those approaches result in the complex design of the system and/or complex modeling of electrostatic field and flow patterns in order to optimize the nozzles array of the multi-jet electrospinning system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported modifications of multi-jet electrospinning (MES) systems in order to overcome the mutual repulsion effect of polymer solution jets include application of additional electrodes, auxiliary electrodes and specifically designed polymer nozzles arrays [21,24,34]. Most of those approaches result in the complex design of the system and/or complex modeling of electrostatic field and flow patterns in order to optimize the nozzles array of the multi-jet electrospinning system.…”
Section: Discussionmentioning
confidence: 99%
“…The needleless process is divided into two categories depending on the feeding system: confined feeding and unconfined feeding. The difference between the confined and unconfined needleless electrospinning is the fact that in confined electrospinning the electrospun fluid is enclosed in a reservoir such as an insulating tube [98,104,105] or any other material in which the polymer is protruded, whereas in unconfined systems there is no reservoir for the spinning solution and the droplets are projected naturally from the surface of the solution. The replacement of the needles in multi-jet spinning is the most convenient way to resolve the complexity and difficulties without compromising the mass throughput [92,99].…”
Section: Needleless Electrospinning 421 Confined Needleless Electrmentioning
confidence: 99%
“…Using microfluidic channels, Srinivasta et al [16] have demonstrated intricate janus architecture nanofibers, but Open Access *Correspondence: sfang@ufl.edu; ykyoon@ece.ufl.edu 1 Electrical and Computer Engineering, University of Florida, 225 Larsen Hall, Gainesville, FL 32611-6200, USA Full list of author information is available at the end of the article the open channel approach has lowered throughput to 0.1 g/h with 8 nozzles. Also, drilled holes in plastic films [17] and drilled holes into syringe filters [18] have been reported. But these approaches suffer from non-uniformity in nanofiber diameter or not quite scalable.…”
Section: Introductionmentioning
confidence: 99%